Interdigitated transducer ammonia sensors based on nanodiamond/polyaniline thin film. Issue 7 (1st April 2016) - Wu, Zuquan; Chen, Xiangdong; Tian, Xin; Chen, Xinpeng; Li, Ning; Ding, Xing
Abstract : The interdigitated transducers sensor based on nanodiamond (ND)/polyaniline (PANI) thin film for ammonia (NH3 ) sensing is investigated, which is synthesised by in situ chemical oxidative polymerisation. The experimental result reveals that the response of 30ND/PANI thin film sensor is much higher than that of PANI for NH3 gas detection. The ND is homogeneously combined into PANI to form ND/PANI nanocomposite, which may increase the specific surface area and improve the response of ND/PANI sensor. Moreover, the response mechanism of ND/PANI for NH3 gas detection is discussed. The synthesised thin films are characterised by Fourier transform infrared spectroscopy and SEM.